A clinicopathological patterns in hysterectomies in a medical college in eastern Nepal - Chaudhary, Amar Nath; Baral, Gehanath; Subedi, Shanti; Dangol, Chandrika (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: Hysterectomy are being performed in regular basis and its aetiology and histopathological findings are watched and co-related in this study. Methods: This is an observational descriptive study carried out in the Department of Obstetrics and Gynaecology at Nobel Medical College Teaching Hospital Biratnagar for one year from 15 May 2021 to 15 may 2022. All the patients undergoing hysterectomies were analysed for indication, type of procedure, complications and histopathological diagnosis. Results: A total of 456 hysterectomies were performed in a year. Preoperative diagnosis in most of the cases was fibroid uterus. The common surgical procedure was total abdominal hysterectomy. The most common histopathological diagnosis was fibroid uterus followed by uterine prolapse, ovarian mass, endometrial disease and adenomyosis. Conclusions: Fibroid uterus is the leading cause of hysterectomy as well as the commonest pathologic diagnosis followed by prolapsed uterus and ovarian tumor. Key words: Adenomyosis, AUB, histopathology, hysterectomy, fibroid, uterus